Radioimmunotherapy Combined With Low-Intensity Ultrasound and Microbubbles: A Potential Novel Strategy for Treatment of Solid Tumors - Lin, Binwei; Du, Huan; Fan, Jinjia; Huang, Dan; Gao, Feng; Li, Jie; Zhang, Yu; Feng, Gang; Dai, Tangzhi; Du, Xiaobo (Frontiers in Oncology, 2021)
The prognosis of advanced malignant tumors is very poor, and effective treatment is limited. Radioimmunotherapy (RIT) is a novel treatment method. However, its anti-tumor effect is poor in solid tumors, which is mainly due to the blood-tumor barrier preventing RIT from entering the tumor, resulting in an insufficient dose. Low-intensity ultrasound combined with microbubbles (USMB) has proven capable of opening the blood-tumor barrier. The combination of the two technologies may overcome the poor anti-tumor effect of RIT and promote the clinical application of RIT in solid tumors. This article reviewed the current research status of RIT in the treatment of solid tumors and the opportunities and challenges of USMB combined with RIT.